High-conductivity conductive silver paste and preparation method thereof

The sheet silver powder prepared by the lac resin template method and the chemical deposition method is mixed with the spherical silver powder, which solves the problem of reduced conductivity caused by the ball milling method, and realizes high conductivity and low cost conductive silver paste, with higher volume filling rate and shorter electron transmission path.

CN120565153APending Publication Date: 2025-08-29QIHUA OPTRONICSKUNSHAN CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510790350.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-13
Publication Date
2025-08-29

AI Technical Summary

Technical Problem

The sheet silver powder prepared by ball milling in the prior art has problems with rough surface, uneven thickness and lubricant residue, resulting in poor connection of conductive paths and reduced conductivity.

Method used

The lac resin template method was used to prepare sheet silver powder with concentrated particle size, thinner thickness and smooth surface with smooth particle surface, and mixed with spherical silver powder to form a closely stacked conductive network. By coating the surface of the silver powder with stearic acid or oleamine to prevent oxidation and reduce contact resistance.

Benefits of technology

The conductivity and printing uniformity of conductive silver paste are improved, the amount and cost of silver powder are reduced, and the agglomeration caused by electron scattering and mechanical interlocking is reduced, achieving higher volume filling rate and shorter electron transmission paths.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120565153A_ABST
    Figure CN120565153A_ABST
Patent Text Reader

Abstract

The invention provides high-conductivity conductive silver paste and a preparation method thereof, the conductive silver paste comprises silver powder, glass powder, an organic carrier and a conductive enhancer, the silver powder comprises spherical silver powder and flake silver powder, the average particle size of the flake silver powder is 5-10 [mu] m, the average thickness is 80-100 nm, and the surface roughness is RMSlt; the wavelength is 10 nm. The conductive silver paste is prepared by selecting the flaky silver powder which is concentrated in particle size, thinner in thickness and smooth in surface, the flaky silver powder can be matched with the spherical silver powder to be tightly stacked in the paste to form'face-face 'and'face-point' conductive networks, the electron transmission path is shorter, the contact resistance is reduced, and the conductivity of the silver paste is effectively improved; the ultra-thin structure can achieve a higher volume filling rate, the use amount of silver powder can be reduced by at least 10% under the same conductivity, and the cost is effectively reduced; meanwhile, the smooth surface reduces electron scattering, the contact resistance is reduced, agglomeration caused by mechanical interlocking is effectively reduced, and uniform printing of the conductive silver paste is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of conductive silver paste, in particular to a highly conductive conductive silver paste and a preparation method thereof. Background Art

[0002] Conductive silver paste is a crucial electrical and thermally conductive connection material, widely used in high-power LED chips, solar panels, flat-panel display panel wiring connections, RFID tags, touchscreen border routing, and membrane switches. In recent years, with the rapid development of industries such as flexible displays, capacitive touch screens, and thin-film solar cells, academic and industrial demands for silver paste performance have continued to rise. High-performance silver paste materials have become a key material for technological development in various fields.

[0003] Conductive silver paste is typically made by mixing silver powder, glass powder, an organic vehicle, and a plasticizer into a paste-like slurry. This paste is then screen-printed onto a substrate to form a conductive pattern. To further enhance conductivity, adding a certain amount of flake silver powder to replace the spherical silver powder used for point contact can effectively improve the paste's conductivity.

[0004] Currently, there are many methods for preparing flaky silver powder, including mechanical ball milling, polyol method, liquid-phase reduction method, soft colloid template method, photoinduction method, and electrochemical method. Mechanical ball milling is the most widely used method in industrial manufacturing. However, ball milling can lead to a series of problems such as surface roughness, uneven thickness, and lubricant residue. This affects the surface-to-surface and surface-to-line connections of ball-milled flaky silver powder when used as a conductive filler, resulting in poor conductive pathway connectivity and reduced conductivity.

[0005] Therefore, how to further improve the performance of conductive silver paste is still an urgent problem to be solved in conductive silver paste. Summary of the Invention

[0006] In view of the shortcomings of the prior art described above, the object of the present invention is to provide a highly conductive conductive silver paste to address the drawbacks of the prior art method of adding flaky silver powder to improve conductivity, such as the problems of rough surface, uneven thickness, and lubricant residue in ball-milled flaky silver powder. At the same time, the present invention will also provide a method for preparing the highly conductive conductive silver paste.

[0007] To achieve the above-mentioned and other related purposes, the present invention provides the following technical solutions: In a first aspect of the present invention, a highly conductive conductive silver paste is provided, comprising silver powder, glass powder, an organic vehicle, and a conductive enhancer. The silver powder comprises spherical silver powder and flaky silver powder. The flaky silver powder has an average particle size of 5 to 10 μm, an average thickness of 80 to 100 nm, and a surface roughness RMS <10 nm.

[0008] The flaky silver powder selected in the present invention has a concentrated particle size, a thinner thickness, and a smooth surface. It can construct a stacked, surface-to-surface conductive network in the conductive silver paste, establishing a high-speed channel for electron transmission, and has the advantage of high conductivity. Its ultra-thin structure can achieve a higher volume filling rate, and can reduce the amount of silver powder used by at least 10% under the same conductivity, effectively reducing costs. At the same time, its smooth surface reduces electron scattering, reduces contact resistance, effectively reduces agglomeration caused by mechanical interlocking, and ensures uniform printing of the conductive silver paste.

[0009] Furthermore, the flaky silver powder is obtained by the following preparation method: (1) Natural shellac resin and a plasticizer are mixed and dissolved in ethanol to obtain a resin solution, which is screen-printed on a PET substrate and dried to obtain a PET / shellac composite film; (2) The PET / lac composite film was first roughened in a potassium permanganate-sulfuric acid solution, and then the surface of the composite film was modified by an aqueous solution of sodium dodecyl sulfate (SDS), and then the composite film was sensitized by an acidic aqueous solution of stannous chloride to obtain a sacrificial film layer; (3) depositing a silver film on the sacrificial film layer by chemical deposition to obtain a silver / polymer composite film; (4) Immersing the silver / polymer composite film in anhydrous ethanol for a period of time, and then using ultrasonic force to peel off the silver film to obtain large silver flakes; (5) mixing the large silver flakes with ethanol to obtain a crude silver powder mixture, and crushing the crude silver powder mixture using a cell crusher; (6) Purifying and drying the crushed silver powder to obtain the flaky silver powder.

[0010] Furthermore, in step (1), the plasticizer is selected from glycerol, dioctyl phthalate, acetyl triethyl citrate or castor oil; the mass ratio of the natural shellac resin to the plasticizer is (6:4) to (9:1); The solid content of the resin solution is 12~18wt%; After screen printing, dry at 120℃ for 30s. At this time, the resin has good leveling properties and a smooth surface. After subsequent treatment, it promotes the flatness of the chemically deposited silver film.

[0011] Furthermore, in step (2), the roughening treatment includes: soaking the PET / shellac composite film in a potassium permanganate-sulfuric acid solution at 60°C for 5 min, then soaking it in an oxalic acid-sulfuric acid solution at 55°C for 60 s, then rinsing it with clean water, and then soaking it in a sodium bicarbonate solution with a pH of 9 at room temperature for 10 min to neutralize the surface acidity; The surface modification treatment includes: immersing the roughened PET / shellac composite film in a 0.1% SDS aqueous solution for 5 minutes, rinsing with deionized water, and drying; The sensitization treatment includes: adding stannous chloride to concentrated hydrochloric acid, mixing well, and then adding deionized water to dilute to obtain a sensitizing solution. At room temperature, the PET / shellac composite film is immersed in the sensitizing solution and allowed to stand for 5 minutes. The film is then taken out, rinsed with deionized water, and dried.

[0012] Furthermore, in step (3), the chemical deposition method includes: uniformly mixing the silver salt solution and the reducing agent solution, and depositing the silver salt solution on the sacrificial film layer by spraying; The amount of silver salt solution and reducing agent solution used per square centimeter of sacrificial film layer is 1 mL each; The silver salt solution includes silver nitrate, sodium hydroxide and ethanol, and the concentrations of the three are 10 g / L, 0.5 g / L and 40 mL / L respectively; The reducing agent solution includes a glucose solution and a potassium sodium tartrate solution, and the concentrations of the glucose solution and the potassium sodium tartrate solution are 10 g / L and 2.5 g / L, respectively.

[0013] Furthermore, in step (4), the soaking time is 5 min to 10 min.

[0014] Furthermore, in step (5), the solid content of the coarse silver powder mixture is 0.1%; The pulverization time is 15-60 min. When the ultrasonic pulverization time is 15 min, the average particle size of the flaky silver powder is 10 μm. As the ultrasonic time increases, the average particle size gradually decreases. When the pulverization time is extended to 60 min, the average particle size drops to 5 μm.

[0015] Furthermore, in step (6), the purification includes: after the pulverized silver powder mixture is centrifuged to remove ethanol, ethyl acetate, ethanol, acetone or toluene-ethanol mixed solvent is added, soaked for 30 minutes, and washed five times by centrifuge at 4000 rpm.

[0016] Furthermore, the amount of the flaky silver powder added to the conductive silver paste is 5-25 wt %.

[0017] Furthermore, the conductive silver paste includes 40-60 wt% of spherical silver powder, 5-25 wt% of flaky silver powder, 5-25 wt% of organic vehicle, 1-10 wt% of glass powder and 0.1-1 wt% of conductivity enhancer.

[0018] Furthermore, the mass ratio of the spherical silver powder to the flaky silver powder is (2:1) to (6:1).

[0019] Furthermore, the particle size of the spherical silver powder is 1-3 μm.

[0020] Furthermore, the silver powder is coated with stearic acid or oleylamine in an amount of 0.1-1% of the mass of the silver powder. By coating the silver powder with a single layer of stearic acid or oleylamine, oxidation can be prevented, the resistivity of the silver powder can be maintained unchanged, and its dispersibility in the slurry can be improved.

[0021] Furthermore, the organic vehicle includes a solvent, an organic resin binder and a dispersant.

[0022] Furthermore, the solvent includes at least one of terpineol, toluene, p-xylene, benzyl alcohol, diethylene glycol monobutyl ether, diethylene glycol dibutyl ether, diethylene glycol butyl ether acetate, tributyl citrate, tributyl phosphate, and p-phenylene ether; The organic resin binder includes at least one of ethyl cellulose, methyl cellulose, hydroxyethyl cellulose, cellulose acetate propionate, acrylic resin, polyurethane resin, polyvinyl alcohol, polystyrene, petroleum resin, polyvinyl pyrrolidone, and polymethyl methacrylate; The dispersant is a hyperbranched polyester dispersant, and the hyperbranched polyester dispersant includes at least one of BYK-2150, BYK-2152, TEGO Dispers 755, and TEGO Dispers 685.

[0023] Furthermore, in the organic vehicle, the organic resin binder accounts for 0.1-30% of the mass of the organic vehicle, and the dispersant accounts for 1-20% of the mass of the organic vehicle.

[0024] Furthermore, the composition of the glass powder is TeO2-ZnO-Bi2O3, and the particle size of the glass powder is less than 100 nm.

[0025] Furthermore, the conductivity enhancer includes carbon nanotubes or graphene.

[0026] A second aspect of the present invention provides a method for preparing a highly conductive silver paste, comprising the following steps: S1. Weigh spherical silver powder and flake silver powder in proportion and mix them under nitrogen protection; S2. Weigh a solvent, an organic resin binder, and a dispersant in proportion, mix them evenly, and stir them at a temperature of 40 to 100° C. for at least 1 hour to obtain an organic vehicle; S3, performing high shear dispersion on the glass powder, the conductive enhancer and the organic vehicle obtained in step S2 under vacuum conditions; S4, adding the composite silver powder of step S1 to the mixture obtained in S3, mixing evenly, rolling with three rollers to a fineness of ≤10 μm, and obtaining the highly conductive conductive silver paste after degassing and filtration.

[0027] Furthermore, in step S1, the mixed composite silver powder is added to a stearic acid ethanol solution or an oleylamine n-hexane solution for surface modification, thereby coating the surface of the silver powder with a monolayer of stearic acid or oleylamine.

[0028] Furthermore, in step S2, the stirring speed is 200-800 rpm.

[0029] Furthermore, in step S3, the rotation speed of the high shear dispersion is 2000-5000 rpm, and the time is 30-60 min.

[0030] Furthermore, in step S4, the roller gap pressure of the three-roll rolling is 0.2-0.5 MPa, and the number of rolling times is ≥3 times.

[0031] As described above, the highly conductive conductive silver paste and the preparation method thereof of the present invention have the following beneficial effects: 1. The present invention uses flaky silver powder with concentrated particle size, thinner thickness and smooth surface to prepare conductive silver paste. The flaky silver powder can cooperate with spherical silver powder to tightly stack in the paste to form "surface-to-surface" and "surface-to-point" conductive networks, which shortens the electron transmission path, reduces contact resistance, and effectively improves the conductivity of the silver paste; and its ultra-thin structure can achieve a higher volume filling rate, which can reduce the amount of silver powder used by at least 10% under the same conductivity, effectively reducing costs; at the same time, its smooth surface reduces electron scattering, reduces contact resistance, effectively reduces agglomeration caused by mechanical interlocking, and ensures uniform printing of the conductive silver paste.

[0032] 2. The present invention uses a shellac resin template method combined with chemical deposition to prepare flaky silver powder with an average thickness of 80-100nm and a surface roughness RMS <10nm, solving the problems of uneven thickness, rough surface and small aspect ratio of flaky silver powder caused by the traditional ball milling method. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 Shown is a SEM image of the flaky silver powder prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0034] The following describes the implementation of the present invention through specific embodiments. People skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.

[0035] Example 1 A flaky silver powder is obtained by the following preparation method: (1) Natural shellac resin and acetyl triethyl citrate in a mass ratio of 9:1 were mixed and dissolved in ethanol to obtain a resin solution with a solid content of 15 wt %. The resin solution was screen-printed on a PET substrate and dried at 120 °C for 30 s to obtain a PET / shellac composite film. (2) Soak the PET / lac composite film in a 38 mM potassium permanganate-sulfuric acid solution at 60 °C for 5 min, then soak it in a 0.3 M oxalic acid-sulfuric acid solution at 55 °C for 60 s, rinse it with clean water, and then soak it in a sodium bicarbonate solution with a pH of 9 for 10 min at room temperature to neutralize the surface acidity; then soak the roughened PET / lac composite film in a 0.1% SDS aqueous solution for 5 min, rinse it with deionized water, and dry it; add 10 g of stannous chloride to 10 mL of 37% concentrated hydrochloric acid, mix it evenly, and then add deionized water to dilute it to 1 L to obtain a sensitizing solution. Immerse the PET / lac composite film in the sensitizing solution at room temperature for 5 min, then take it out, rinse it with deionized water, and dry it; (3) preparing a silver salt solution including 10 g / L silver nitrate, 0.5 g / L sodium hydroxide and 40 mL / L ethanol, and preparing a reducing agent solution including 10 g / L glucose solution and 2.5 g / L potassium sodium tartrate solution, mixing the silver salt solution and the reducing agent solution evenly, and depositing them on the sacrificial film layer by spraying. The amount of silver salt solution and reducing agent solution used per square centimeter of the sacrificial film layer is 1 mL each, to obtain a silver / polymer composite film; (4) Immersing the silver / polymer composite film in anhydrous ethanol for 5 minutes, and then using ultrasonic force to peel off the silver film to obtain large silver flakes; (5) The large silver flakes were initially crushed and mixed with ethanol to prepare a coarse silver powder mixture with a solid content of 0.1%, and the coarse silver powder mixture was crushed using a 480W cell crusher for 60 minutes; (6) The pulverized silver powder mixture was centrifuged to remove ethanol, and then ethyl acetate, ethanol, acetone, and a toluene-ethanol mixed solvent were added, each of which was soaked for 30 minutes, and the mixture was cleaned five times by centrifuge at 4000 rpm; the washed flaky silver powder was dried in an oven at 40°C for 48 hours, and the solvent was evaporated to obtain the flaky silver powder.

[0036] like Figure 1 As shown, according to SEM detection, the average particle size of the flaky silver powder is 5 μm, the flake rate is 100%, the average thickness is 85 nm, and the surface roughness RMS is 4.9 nm, which indicates that the flaky silver powder prepared by the present invention has a smooth surface, uniform thickness, and a large diameter-to-thickness ratio.

[0037] Example 2 A highly conductive silver paste comprises 60 wt% of spherical silver powder (average particle size 2 μm), 10 wt% of flaky silver powder prepared in Example 1, 18 wt% of terpineol, 6 wt% of ethyl cellulose, 0.5 wt% of BYK-2152, 5 wt% of nano-glass powder, and 0.5 wt% of carbon nanotubes. The preparation method comprises the following steps: S1. Weighing spherical silver powder and flaky silver powder in proportion and mixing them under nitrogen protection to obtain composite silver powder; S2. Weigh terpineol, ethyl cellulose, and BYK-2152 in proportion, mix them evenly, and stir them at 60° C. and 500 rpm for at least 1 hour to obtain an organic vehicle; S3, performing high shear dispersion on the glass powder, carbon nanotubes and the organic carrier obtained in step S2 under vacuum conditions; S4, adding the composite silver powder of step S1 to the mixture obtained in S3, mixing evenly, rolling with three rollers to a fineness of ≤10 μm, and obtaining the highly conductive conductive silver paste after degassing and filtration.

[0038] Example 3 A highly conductive silver paste comprises 60 wt% of spherical silver powder (average particle size 2 μm), 10 wt% of flaky silver powder prepared in Example 1, 18 wt% of terpineol, 6 wt% of ethyl cellulose, 0.5 wt% of BYK-2152, 5 wt% of nano-glass powder, and 0.5 wt% of carbon nanotubes. The preparation method comprises the following steps: S1. Weighing spherical silver powder and flaky silver powder in proportion and mixing them under nitrogen protection to obtain composite silver powder; adding the composite silver powder to a 1 wt % stearic acid ethanol solution at 60° C. and stirring at 200 rpm for 2 h, thereby coating the surface of the silver powder with a monolayer of stearic acid, followed by centrifugation, washing with ethanol three times, and drying to obtain coated silver powder; S2. Weigh terpineol, ethyl cellulose, and BYK-2152 in proportion, mix them evenly, and stir them at 60° C. and 500 rpm for at least 1 hour to obtain an organic vehicle; S3, performing high shear dispersion on the glass powder, carbon nanotubes and the organic carrier obtained in step S2 under vacuum conditions; S4, adding the coated silver powder of step S1 to the mixture obtained in S3 and mixing evenly, rolling with three rollers to a fineness of ≤10 μm, and obtaining the highly conductive conductive silver paste after degassing and filtration.

[0039] Example 4 A highly conductive silver paste comprises 60 wt% of spherical silver powder (average particle size 2 μm), 25 wt% of flaky silver powder prepared in Example 1, 7 wt% of terpineol, 2 wt% of ethyl cellulose, 0.5 wt% of BYK-2152, 5 wt% of nano-glass powder (80 nm), and 0.5 wt% of carbon nanotubes. The preparation method comprises the following steps: S1. Weighing spherical silver powder and flaky silver powder in proportion and mixing them under nitrogen protection to obtain composite silver powder; S2. Weigh terpineol, ethyl cellulose, and BYK-2152 in proportion, mix them evenly, and stir them at 60° C. and 500 rpm for at least 1 hour to obtain an organic vehicle; S3, performing high shear dispersion on the glass powder, carbon nanotubes and the organic carrier obtained in step S2 under vacuum conditions; S4, adding the composite silver powder of step S1 to the mixture obtained in S3, mixing evenly, rolling with three rollers to a fineness of ≤10 μm, and obtaining the highly conductive conductive silver paste after degassing and filtration.

[0040] Comparative Example 1 A conductive silver paste comprising 60 wt% of spherical silver powder (average particle size 2 μm), commercially available flaky silver powder (average particle size 5 μm), 18 wt% of terpineol, 6 wt% of ethyl cellulose, 0.5 wt% of BYK-2152, 5 wt% of nano-glass powder, and 0.5 wt% of carbon nanotubes; a preparation method thereof comprising the following steps: S1. Weighing spherical silver powder and flaky silver powder in proportion and mixing them under nitrogen protection to obtain composite silver powder; S2. Weigh terpineol, ethyl cellulose, and BYK-2152 in proportion, mix them evenly, and stir them at 60° C. and 500 rpm for at least 1 hour to obtain an organic vehicle; S3, performing high shear dispersion on the glass powder, carbon nanotubes and the organic carrier obtained in step S2 under vacuum conditions; S4, adding the composite silver powder of step S1 to the mixture obtained in S3, mixing evenly, rolling with three rollers to a fineness of ≤10 μm, and obtaining the conductive silver paste after degassing and filtration.

[0041] Performance test: The conductive silver pastes prepared in Examples 2 to 4 and Comparative Example 1 were screen printed, dried, and sintered to obtain conductive patterns. The performance of the samples was then tested. The test results are shown in Table 1.

[0042] Table 1. Properties of the conductive silver pastes of Examples 2 to 4 and Comparative Example 1

[0043] The test results show that the flaky silver powder prepared by the present invention has ideal surface-to-surface contact and good stacking arrangement in the conductive paste, has the advantages of low filling amount and high conductivity, and can greatly improve the conductivity of the silver paste; and, combined with the surface coating of the silver powder, can further improve the leveling and uniformity of the silver paste, thereby improving the printing performance of the silver paste.

[0044] In summary, the present invention uses flaky silver powder with a concentrated particle size, thinner thickness, and smooth surface to prepare conductive silver paste. This flaky silver powder can be tightly stacked with spherical silver powder in the paste to form a "surface-to-surface" and "surface-to-point" conductive network, shortening the electron transmission path and reducing contact resistance, effectively improving the conductivity of the silver paste. Its ultra-thin structure can achieve a higher volume filling rate, reducing the amount of silver powder used by at least 10% at the same conductivity, effectively reducing costs. At the same time, its smooth surface reduces electron scattering, reduces contact resistance, effectively reduces agglomeration caused by mechanical interlocking, and ensures uniform printing of the conductive silver paste. Therefore, the present invention effectively overcomes the various shortcomings of the existing technology and has high industrial utilization value.

[0045] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the present invention. Anyone skilled in the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by one of ordinary skill in the art without departing from the spirit and technical principles disclosed herein are intended to be covered by the claims of the present invention.

Claims

1. A highly conductive silver paste, characterized in that: The invention comprises silver powder, glass powder, organic carrier and conductive enhancer. The silver powder comprises spherical silver powder and flaky silver powder. The average particle size of the flaky silver powder is 5-10 μm, the average thickness is 80-100 nm, and the surface roughness RMS is less than 10 nm.

2. The conductive silver paste according to claim 1, characterized in that The flaky silver powder is obtained by the following preparation method: (1) Natural shellac resin and a plasticizer are mixed and dissolved in ethanol to obtain a resin solution, which is screen-printed on a PET substrate and dried to obtain a PET / shellac composite film; (2) The PET / lac composite film was first roughened in a potassium permanganate-sulfuric acid solution, and then the surface of the composite film was modified by an aqueous solution of sodium dodecyl sulfate (SDS), and then the composite film was sensitized by an acidic aqueous solution of stannous chloride to obtain a sacrificial film layer; (3) depositing a silver film on the sacrificial film layer by chemical deposition to obtain a silver / polymer composite film; (4) Immersing the silver / polymer composite film in anhydrous ethanol for a period of time, and then using ultrasonic force to peel off the silver film to obtain large silver flakes; (5) mixing the large silver flakes with ethanol to obtain a crude silver powder mixture, and crushing the crude silver powder mixture using a cell crusher; (6) Purifying and drying the crushed silver powder to obtain the flaky silver powder.

3. The conductive silver paste according to claim 2, characterized in that In step (1), the plasticizer is selected from glycerol, dioctyl phthalate, acetyl triethyl citrate or castor oil; the mass ratio of the natural shellac resin to the plasticizer is (6:4) to (9:1).

4. The conductive silver paste according to claim 2, characterized in that In step (2), the roughening treatment includes: soaking the PET / shellac composite film in a potassium permanganate-sulfuric acid solution at 60°C for 5 minutes, then soaking it in an oxalic acid-sulfuric acid solution at 55°C for 60 seconds, then rinsing it with clean water, and then soaking it in a sodium bicarbonate solution with a pH of 9 at room temperature for 10 minutes to neutralize the surface acidity; The surface modification treatment includes: immersing the roughened PET / shellac composite film in a 0.1% SDS aqueous solution for 5 minutes, rinsing with deionized water, and drying; The sensitization treatment includes: adding stannous chloride to concentrated hydrochloric acid, mixing well, and then adding deionized water to dilute to obtain a sensitizing solution. At room temperature, the PET / shellac composite film is immersed in the sensitizing solution and allowed to stand for 5 minutes. The film is then taken out, rinsed with deionized water, and dried.

5. The conductive silver paste according to claim 2, characterized in that In step (3), the chemical deposition method includes: mixing a silver salt solution and a reducing agent solution uniformly, and depositing them on the sacrificial film layer by spraying; wherein, the amount of the silver salt solution and the reducing agent solution used per square centimeter of the sacrificial film layer is 1 mL each; the silver salt solution includes silver nitrate, sodium hydroxide and ethanol, and the reducing agent solution includes glucose solution and potassium sodium tartrate solution.

6. The conductive silver paste according to any one of claims 1 to 5, characterized in that The surface of the silver powder is coated with stearic acid or oleylamine, and the coating amount is 0.1-1% of the mass of the silver powder.

7. The conductive silver paste according to any one of claims 1 to 5, characterized in that The organic vehicle includes a solvent, an organic resin binder and a dispersant; the solvent includes at least one of terpineol, toluene, p-xylene, benzyl alcohol, diethylene glycol monobutyl ether, diethylene glycol dibutyl ether, diethylene glycol butyl ether acetate, tributyl citrate, tributyl phosphate, and p-phenylene ether; the organic resin binder includes at least one of ethyl cellulose, methyl cellulose, hydroxyethyl cellulose, cellulose acetate propionate, acrylic resin, polyurethane resin, polyvinyl alcohol, polystyrene, petroleum resin, polyvinyl pyrrolidone, and polymethyl methacrylate; the dispersant is a hyperbranched polyester dispersant, and the hyperbranched polyester dispersant includes at least one of BYK-2150, BYK-2152, TEGO Dispers 755, and TEGO Dispers 685.

8. The conductive silver paste according to any one of claims 1 to 5, characterized in that The conductivity enhancer includes carbon nanotubes or graphene.

9. The method for preparing a highly conductive silver paste according to any one of claims 1 to 8, wherein: The following steps are involved: S1. Weigh spherical silver powder and flake silver powder in proportion and mix them under nitrogen protection; S2. Weigh a solvent, an organic resin binder, and a dispersant in proportion, mix them evenly, and stir them at a temperature of 40 to 100° C. for at least 1 hour to obtain an organic vehicle; S3, performing high shear dispersion on the glass powder, the conductive enhancer and the organic vehicle obtained in step S2 under vacuum conditions; S4, adding the composite silver powder of step S1 to the mixture obtained in S3 and mixing evenly, rolling with three rollers to a fineness of ≤10 μm, and obtaining the highly conductive conductive silver paste after degassing and filtration.

10. The conductive silver paste according to claim 9, characterized in that: In step S1, the mixed composite silver powder is added to a stearic acid ethanol solution or an oleylamine n-hexane solution for surface modification, thereby coating the surface of the silver powder with a monolayer of stearic acid or oleylamine.